Znalostní management a jeho uplatnění v menších podnicích - Novotný, Josef; Mikulecký, Peter (Univerzita Pardubice, 2011)
Knowledge management and its support by modern information and communication technologies is a relatively recent but still very topical area. The knowledge has already become a critical strategic resource for business activities and further economic development of firms and whole society too. Thanks to knowledge management as well as efficient exploitation of shared corporate knowledge various firms can develop their competitive advantages more and more. In the Czech Republic the interest in knowledge management utilization is mainly connected with international firms. In this paper we wish to show on a case of a smaller Czech firm that knowledge management can be an appropriate choice also for small and mediumsized enterprises.
Keywords: knowledge management; small -size enterprises; medium-size enterprises; knowledge; practice